2022
DOI: 10.3390/ijerph192114474
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Desire for Psychological Support When Receiving a Cancer Diagnostic

Abstract: Background: Factors related to the desire of receiving psychological help in cancer patients are not well known. The aim of this study is to assess the prevalence of patients who would ask for psychological assistance in the first weeks following diagnosis, and to identify their psychosocial and disease-related profile. Method: This cross-sectional study assessed 229 consecutive cancer outpatients at a visit with their oncologist to be informed about the treatment they will receive. Disease-related and medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, psychological support assumes paramount importance for patients grappling with the multifaceted challenges associated with PMP treatment. Counselling services and support groups offer a nurturing environment wherein patients can find solace, navigate the intricacies of their diagnosis and treatment, and fortify their overall well-being throughout the treatment trajectory [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, psychological support assumes paramount importance for patients grappling with the multifaceted challenges associated with PMP treatment. Counselling services and support groups offer a nurturing environment wherein patients can find solace, navigate the intricacies of their diagnosis and treatment, and fortify their overall well-being throughout the treatment trajectory [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…In another study, the percentage of patients with an over threshold level of psychosocial distress and the subjective desire for psychoonoclogical varies between 13.7% during acute care hospital and 18.2% three months after discharge (Herbert et al 2020 ). Other analyses showed a desire for support in 20% of cancer patients (Blasco, Jovell, Mirapeix, & Leon, 2022 ), or in 32% (Faller et al 2016 ), respectively. A study of patients receiving chemotherapy showed that the desire for psychooncological support was associated with distress, anxiety, and depression (Baker-Glenn et al 2011 ).…”
Section: Introductionmentioning
confidence: 96%
“…Young people encounter a broad spectrum of tumor types or other malignancies, which occur during a critical developmental period [19,36]. Despite this heterogeneity in diagnosis, emotional distress is consistently observed in this population [37,38]. Studies have shown there is an increase in affective disorders at diagnosis which can still be present up to a year later [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…For young people, these barriers may be further compounded by the degree of distress inherent in cancer, and the biographical disruptions inherent to its diagnosis [21,48]. The exact nature of these barriers is still not fully understood [44] but may relate to the type of support that is offered, i.e., 1-to-1 therapies vs. group therapy, in-person vs. online, or a lack of understanding of what psychological support entails [37]. Young people are at risk of not being able to verbalize this distress due to their developmental age and emotional awareness [20,49].…”
Section: Introductionmentioning
confidence: 99%